Penyimpanan Arsip Elektronik Berbasis Dashbaord Interaktif pada Arsip Terjaga di Dispendukcapil Kota Malang - Amalia, Salma; Fatkhur Rochman (STIKes Ibnu Sina Ajibarang, 2025)
Dispendukcapil Kota Malang is is a government agency responsible for managing population administration, including civil registration records or archived documents. As the volume of archives, especially birth certificate registration files, electronic archive storage has become important to ensure that the information contained therein can be accessed and used. This study focuses on the development of an interactive dashboard-based electronic record storage application using VBA Ms. Excel, with the aim of simplifying the complex Ms. Excel interface, facilitating the data input process and record search that was previously done manually, and accelerating reporting related to records. This action research involved eight respondents, consisting of two computer experts, two archive experts, three potential users or archivists, and one archivist supervisor using the Technology Acceptance Model (TAM). The research was conducted in two cycles, each cycle covering the planning, implementation, observation, and reflection stages. The results of Cycle I showed that the developed application received an average score of 90% in the “very suitable” category; however, there were suggestions for improvement, leading to the continuation of Cycle II. The results of Cycle II achieved an average score of 91% in the “very suitable” category. The results of the study show that respondents agree with the indicators of perceived ease and perceived usefulness based on acceptance of IT.